2020
DOI: 10.1161/circheartfailure.118.005853
|View full text |Cite
|
Sign up to set email alerts
|

Early Escalation of Mechanical Circulatory Support Stabilizes and Potentially Rescues Patients in Refractory Cardiogenic Shock

Abstract: Background: Limited progress has been made in the management of cardiogenic shock (CS). Morbidity and mortality of refractory CS remain high. The effects of mechanical circulatory support (MCS) are promising, although many aspects are elusive. We evaluated efficacy and safety of early combined MCS (Impella microaxial pump + venoarterial extracorporeal membrane oxygenation [VA-ECMO]) in refractory CS and aimed to determine factors for decision-making in combined MCS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 42 publications
1
64
1
Order By: Relevance
“…Written informed consent was obtained from legal guardians during the unconscious period and re-consented by survivors after gaining consciousness. HACORE includes anonymized data from all OHCA patients treated at our cardiac arrest centre with a standardized protocol including therapeutic hypothermia and mechanical circulatory support if required [1,[12][13][14][15]. In the present analysis, all OHCA patients undergoing implantation of V-A ECMO for eCPR between January 2018 and December 2019 were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consent was obtained from legal guardians during the unconscious period and re-consented by survivors after gaining consciousness. HACORE includes anonymized data from all OHCA patients treated at our cardiac arrest centre with a standardized protocol including therapeutic hypothermia and mechanical circulatory support if required [1,[12][13][14][15]. In the present analysis, all OHCA patients undergoing implantation of V-A ECMO for eCPR between January 2018 and December 2019 were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…This may explain inferior survival outcomes in studies using Impella. In a recent study by Tongers et al [2], using Impella with VA ECMO showed 30-day survival rate of 49% and 6-month survival rate of 40%. Another study from Berlin [3] used Impella for left-sided mechanical circulatory support (MCS) and showed 37% in-hospital survival rate.…”
Section: Role Of Impellamentioning
confidence: 96%
“…Although the prediction of refractory CS to an individual clinical situation will always remain a challenge, the identification of risk factors of outcome might ease the communication of objective prognostic information to family members and surrogate decision makers, help ICU physicians and interventionists to identify severe CS patients with reasonable chance of survival and reduce of futile healthcare. Lactate is a well-known predictor of mortality in cardiogenic shock and serves as an independent predictor in setting of severe CS treated with Impella or VA-ECMO or both [ 42 , 43 , 44 ], while combined use of lactate and pH demonstrated better prognostic capacity than traditional risk scores in patients treated with VA-ECMO for severe shock [ 45 ]. Similarly, vasoactive score served as predictor of mortality in patients treated with Impella 5.0 and biventricular support [ 20 ].…”
Section: Discussionmentioning
confidence: 99%